Improving institutional research ethics capacity assessments: lessons from sub-Saharan Africa. Issue 1 (1st January 2020) - Deutsch-Feldman, Molly; Ali, Joseph; Kass, Nancy; Phaladze, Nthabiseng; Michelo, Charles; Sewankambo, Nelson; Hyder, Adnan A.
ABSTRACT: The amount of biomedical research being conducted around the world has greatly expanded over the past 15 years, with particularly large growth occurring in low- and middle-income countries (LMICs). This increased focus on understanding and responding to disease burdens around the world has brought forth a desire to help LMIC institutions enhance their own capacity to conduct scientifically and ethically sound research. In support of these goals the Johns Hopkins-Fogarty African Bioethics Training Program (FABTP) has, for the past six years, partnered with three research institutions in Africa (University of Botswana, Makerere University in Uganda, and the University of Zambia) to support research ethics capacity. Each partnership began with a baseline evaluation of institutional research ethics environments in order to properly tailor capacity strengthening activities and help direct limited institutional resources. Through the course of these partnerships we have learned several lessons regarding the evaluation process and the framework used to complete the assessments (the Octagon Model). We believe that these lessons are generalizable and will be useful for groups conducting such assessments in the future.